PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI SEBAGAI INDIKATOR PROFESSIONALISME GURU PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Muzayyana; Moh. Rofiqi Afnan; Munawir (STKIP Subang, 2026)
This study aims to analyze the use of technology-based learning media as an indicator of the professionalism of Islamic Education (PAI) teachers in the digital era. The research employs a qualitative approach through library research by reviewing relevant literature sources. The findings indicate that the use of technology in PAI learning plays a significant role in improving learning quality, student interest, creativity, and learning effectiveness. Furthermore, teachers’ ability to integrate technology with pedagogy and subject content reflects a high level of professionalism. However, several challenges remain, including limited digital competence, infrastructure constraints, and teachers’ readiness to adapt. Therefore, continuous training and institutional support are necessary to optimize the implementation of technology-based learning in Islamic education.